Evaluation of Inter-System Variability in Liver Stiffness Measurements - Ferraioli, Giovanna; De Silvestri, Annalisa; Lissandrin, Raffaella; Maiocchi, Laura; Tinelli, Carmine; Filice, Carlo; Barr, Richard G. (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Aim The primary aim of this study was to determine the inter-system variability of liver stiffness measurements (LSMs) in patients with varying degrees of liver stiffness. The secondary aim was to determine the inter-observer variability of measurements.Materials and Methods 21 individuals affected by chronic hepatitis C and 5 healthy individuals were prospectively enrolled. The assessment of LSMs was performed using six ultrasound (US) systems, four of which with point shear wave elastography (p-SWE) and two with 2 D shear wave elastography (2D-SWE) systems. The Fibroscan (Echosens, France) was used as the reference standard. Four observers performed the measurements in pairs (A-B, C-D). The agreement between different observers or methods was calculated using Lin’s concordance correlation coefficient. The Bland-Altman limits of agreement (LOA) were calculated as well.Results There was agreement above 0.80 for all pairs of systems. The mean difference between the values of the systems with 2D-SWE technique was 1.54 kPa, whereas the maximum mean difference between the values of three out of four systems with the pSWE technique was 0.79 kPa. The intra-patient concordance for all systems was 0.89 (95 % CI: 0.83 – 0.94). Inter-observer agreement was 0.96 (95 % CI: 0.94 – 0.98) for the pair of observers A-B and 0.93 (95 % CI: 0.89 – 0.96) for the pair of observers C-D.Conclusion The results of this study show that the agreement between LSMs performed with different US systems is good to excellent and the overall inter-observer agreement in “ideal conditions” is above 0.90 in expert hands.
Keywords: liver stiffness; shear wave elastography; variability studies; cirrhosis; liver fibrosis